EVALUASI KOMPOSISI DAN STRUKTUR VEGETASI TUMBUHAN SEBAGAI PENDUKUNG STRATEGI PENGEMBANGAN EKOWISATA DESA SEI. MEMPURA - Mariana Eddy; Jumiati Jumiati; Ermina Sari (Universitas Sebelas Maret, 2014)
Abstract- This study aims to evaluate of plant composition andvegetation structure inas supporting development strategy ecotourism inSei . Mempura which combines elements of tourism and conservation of nature so that the emphasis on aspects of nature conservation will always be maintained in the absence of concerns about environmental degradation and exploitation . The method used in this study is a survey method of vegetation analysis techniques premises . This research was conducted in Sei . MempuraKab. Siak Sri Indrapura . Data collection was conducted in January 2014 . Based on the results of the analysis of vegetation known that species that dominates the mainstay and economic value and can be highlighted as supporting ecotourism program in the village of SeiMempura is mangosteen ( DR = 9,584 ) and durian ( DR = 8582 ) . The area is famous for its fruit nimanggisnya species that are small and have a very sweet flesh .Spessies durian is also the appeal of Sei. Mempura to attract tourists locally and nationally on a particular season to visit this village. This sector is a strength yangseyogyanya should continue to be encouraged in this area Keywords : Plant structure, vegetation analysis , ecotourism